FliS/flagellin/FliW heterotrimer couples type III secretion and flagellin homeostasis - Florian Altegoer (Nature Portfolio, 2018)
Abstract Flagellin is amongst the most abundant proteins in flagellated bacterial species and constitutes the major building block of the flagellar filament. The proteins FliW and FliS serve in the post-transcriptional control of flagellin and guide the protein to the flagellar type III secretion system (fT3SS), respectively. Here, we present the high-resolution structure of FliS/flagellin heterodimer and show that FliS and FliW bind to opposing interfaces located at the N- and C-termini of flagellin. The FliS/flagellin/FliW heterotrimer is able to interact with FlhA-C suggesting that FliW and FliS are released during flagellin export. After release, FliW and FliS are recycled to execute a new round of post-transcriptional regulation and targeting. Taken together, our study provides a mechanism explaining how FliW and FliS synchronize the production of flagellin with the capacity of the fT3SS to secrete flagellin.